(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
In this scientific paper, the basics of designing beams made from local wood products are studied in detail. In this, glued and whole wooden beams made of local wood materials are studied in classes. Methods for calculating beams made of local wood materials for stretching were also considered. Depending on the types of materials of beams made of local wooden structures, types of all-round, metal-round, glued timber were considered.